ANALISIS STRUKTUR KRISTAL MATERIAL BARIUM HEKSAFERRIT BaFe12-x(CoTi0.5Mn0.5)x/2O19 - Nurul Annisa Kumalahardiyani; Riser Fahdiran; Erfan Handoko (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
Barium hexaferrite with hexagonal molecular BaFe12O19 is one of the magnetic materials that widely used for research, about improving the quality of material corresponding the application. BaFe12O19 has high HC (magnetic saturation), good chemical stability, high TC (Curie temperature) and corrosion resistant. Synthesis material BaFe12-x(CoTi0.5Mn0.5)x/2O19, with x=0 and x=1, made through smoothing BaCO3, Fe2O3, Co3O4, TiO2, and MnCO3 using High Energy Ball Mill for 1 hour by using wet milling method. Then calcinating at temperature of 750°C for 3 hours and sintering at temperature 1100°C for 6 hours. Expected in this material may be formed phases can be identified and analyzed qualitatively and quantitatively using X-Ray Diffractometer (XRD) to identify the crystal structure of the materials and processed using High-Score Plus application. From the XRD chart, known that the substitution ion Mn, Co and Ti has been done. The value of lattice parameter is a = b =5.88 Å, and c = 23.24 Å. Keywords: crystal structure, Barium hexaferrite, X-Ray Diffractometer.